2017
DOI: 10.1371/journal.pone.0179471
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effect of TiF4 and NaF on fibroblasts is influenced by the experimental model, fluoride concentration and exposure time

Abstract: ObjectiveTitanium tetrafluoride (TiF4) has shown promising effect in preventing tooth lesions. Therefore, we compared the cytotoxicity of TiF4 with sodium fluoride (NaF) (already applied in Dentistry) considering different fluoride concentrations, pH values and experimental models.Materials and methodsStep 1) NIH/3T3 fibroblasts were exposed to mediums containing NaF or TiF4 (from 0.15 to 2.45% F), both at native and adjusted pH, for 6 h. Step 2) NIH/3T3 were exposed to NaF or TiF4 varnishes with 0.95, 1.95 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
(68 reference statements)
1
13
0
1
Order By: Relevance
“…Verma et al showed that fluoride concentrations of 120 ppm decreased cell viability up to 60% 57 . Although fluoride is generally considered toxic at concentrations above 15 ppm 41 , 42 , long term exposure (up to 5 days) to non-lethal fluoride concentrations as low as 5 ppb of F - were shown to decrease cellular DNA synthesis and a F - concentration of 38 ppb almost completely inhibited it 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Verma et al showed that fluoride concentrations of 120 ppm decreased cell viability up to 60% 57 . Although fluoride is generally considered toxic at concentrations above 15 ppm 41 , 42 , long term exposure (up to 5 days) to non-lethal fluoride concentrations as low as 5 ppb of F - were shown to decrease cellular DNA synthesis and a F - concentration of 38 ppb almost completely inhibited it 41 .…”
Section: Resultsmentioning
confidence: 99%
“…4. This strongly enhanced UCNP stability is ascribed to the formation of a protective corona of adsorbed biomolecules on the UCNP surface, similar to the formation of a protein corona observed for many nanoparticle systems in plasma and in intracellular fluids which is known to significantly affect nanoparticle toxicity [38][39][40][41][42][43] .…”
Section: Effect Of the Chemical Composition Of The Aqueous Mediummentioning
confidence: 94%
“…Titanium tetrafluoride varnish also promoted higher deposition of calcium fluoride than NaF varnish as a result of its lower pH . Besides, TiF 4 varnish has cytotoxic potential on fibroblasts similarly to NaF varnish, which is widely applied in the mouth . However, there is a lack of knowledge about the protective effect of TiF 4 varnish on root dentine demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its low pH, a TiF 4 varnish is able to enhance the enamel fluoride uptake compared to a NaF varnish [ 10 ]. The varnish may also reduce TiF 4 contact with soft tissues compared to a rinse solution, reducing the possibility of cytotoxicity due to its low pH [ 22 ]. A recent study has shown that a TiF 4 varnish presents similar levels of toxicity to murine fibroblast lineage (NIH/3T3) cells as a NaF varnish [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The varnish may also reduce TiF 4 contact with soft tissues compared to a rinse solution, reducing the possibility of cytotoxicity due to its low pH [ 22 ]. A recent study has shown that a TiF 4 varnish presents similar levels of toxicity to murine fibroblast lineage (NIH/3T3) cells as a NaF varnish [ 22 ]. To check for possible side effects of the TiF 4 varnish, patient satisfaction was evaluated using a simple, but effective tool for self-rated child pain [ 18 ].…”
Section: Discussionmentioning
confidence: 99%